Explicit Language Teaching and Competence in Using the Past Tense in English Among Saudi EFL Learners - Alanazi, Sami (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
It has been well-established in research that Saudi Arabian EFL students tend to find it difficult to understand English tenses. In particular, they struggle with conjugating verbs in the past tense. This research examines how explicit grammar teaching could help undergraduate level Saudi students overcome these difficulties. For the study, students were put into two different groups. These were the experimental group (group A) and the control group (group B). Group A students were given direct, specific teaching focused on learning the past-tense. Group B students were given more general teaching. At the end of the study, they were tested. The results of these tests demonstrate a definite short-term improvement in the ability of group A students, but later testing indicates that this improvement may have been short-lived.